Analysis of buckling behaviour in web girder - Norshamiera Afzan , Ismail (2014)
Normally, an economical and effective design of web plat girder requires thin webs. However, thin and very slender web plat girder will cause it to buckle. Corrugated web girder or Trapezoidal Web Plate (TWP) is used to overcome this situation. This project aims to produce a finite element model and studying the web profile of the beam by using LUSAS Modeller 14.0. There were three model produced to be analyse in this project. The dimension of each model are 1500mm x 200mm x 900mm. Each model is simply supported with fixed support and pinned support. The type of mesh used for each model is Quadrilateral Thin Shell with 8 nodes (QSL8). LUSAS, Modeller 14.0 finite element software is able to carry out linear analysis to determine deformed mesh, maximum stress and strain under axial load. Besides, critical buckling load can be predicted under the linear buckling analysis. The results show that the TWP2 has highest strength compared to TWP 1 and Flat Web beam. The results also show that TWP of web can sustain higher buckling load compared to Flat Web girder.Error! Bookmark not defmed.